2014
DOI: 10.1007/s00125-014-3304-y
|View full text |Cite
|
Sign up to set email alerts
|

Islet amyloid formation is an important determinant for inducing islet inflammation in high-fat-fed human IAPP transgenic mice

Abstract: Aims/hypothesis Amyloid deposition and inflammation are characteristic of islet pathology in type 2 diabetes. The aim of this study was to determine whether islet amyloid formation is required for the development of islet inflammation in vivo. Methods Human islet amyloid polypeptide transgenic mice and non-transgenic littermates (the latter incapable of forming islet amyloid) were fed a low-fat (10%) or high-fat (60%) diet for 12 months; high-fat feeding induces islet amyloid formation in transgenic mice. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 9 publications
3
65
0
Order By: Relevance
“…More recent reports indicate that soluble hIAPP species produced during early hIAPP aggregation are themselves able to activate the TLR2/MyD88 pathway to prime macrophages (82,91), and palmitate priming of inflammasomes has also been reported (92). Additionally, an independent group confirmed the presence of inflammasome markers (Nlrp3, Pycard, and Casp1) and inflammatory cytokines (Il1b, Tnf, and Il6) within islets of hIAPP-Tg mice fed a HFD (80).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…More recent reports indicate that soluble hIAPP species produced during early hIAPP aggregation are themselves able to activate the TLR2/MyD88 pathway to prime macrophages (82,91), and palmitate priming of inflammasomes has also been reported (92). Additionally, an independent group confirmed the presence of inflammasome markers (Nlrp3, Pycard, and Casp1) and inflammatory cytokines (Il1b, Tnf, and Il6) within islets of hIAPP-Tg mice fed a HFD (80).…”
mentioning
confidence: 79%
“…Further analysis of hIAPP-Tg mice revealed that dietary fat promotes islet amyloid formation and that one year on a HFD caused β cell loss and impaired insulin secretion (79). Islets in hIAPP-Tg mice exhibited larger F4/80-positive areas and greater expression of chemokines (Ccl2 and Cxcl1) and macrophage markers (Emr1 and Itgax) than non-transgenic mice after one year on either a low-fat diet or HFD (80). Additionally, immunostaining studies revealed the presence of IAPP within the lysosomes of islet macrophages in hIAPP-Tg mice but not rIAPP-Tg mice, suggesting that macroinflammatory response in the islets, and also demonstrate a role for the autocrine or paracrine effects of IL-1β.…”
Section: Mechanisms Of Islet Inflammation and Inflammation-induced β mentioning
confidence: 99%
“…Our finding that toxic h-IAPP LP intermediates bound RAGE and upregulated β cell RAGE expression led us to predict that LP intermediates would modulate inflammatory gene expression and cytotoxicity in cultured β cells and muscle cells, as h-IAPP-induced islet cell and cardiomyocyte inflammation have been reported (40,42,44,45,51). We also expected that sRAGE would compete with cellsurface RAGE for h-IAPP binding, as it targets toxic LP intermediates and is a competitive inhibitor of ligand binding to cell membrane-bound RAGE.…”
Section: Rage Significantly Contributes To H-iapp-mediated Cellular Pmentioning
confidence: 99%
“…In chronic ER stress, quality control mechanisms that retain misfolded proteins in the ER are relaxed or overwhelmed, allowing misfolded proteins to move to the Golgi and be packaged for secretion . One sign of relaxed ER quality control is the accumulation of misfolded amyloid proteins in the extracellular space, and accumulation of b-amyloid in human pancreatic islets is a well-characterised feature of T2D that has been linked with oxidative stress, inflammatory signalling and apoptosis , Masters et al 2010, Jurgens et al 2011, Meier et al 2014. Relaxation or overwhelming quality control will not only allow secretion of protein products (albeit potentially inappropriately folded) but also reduce the burden on ERAD to dispose of misfolded proteins.…”
Section: Intrinsic Er Functionsmentioning
confidence: 99%